The effectiveness of management accounting systems in SMEs: a multidimensional measurement approach - Pedroso, Elsa do Carmo Santos (2020)
Purpose – The purpose of this paper is to present and validate a multidimensional approach to measure the effectiveness of management accounting systems. Design/methodology/approach – Based on an extensive literature review, the most appropriate information dimensions were identified. To validate the multidimensional tool, survey data were obtained from 284 chief financial officers of Portuguese small and medium-sized enterprises. A structural equation model, evaluating the influence on the managerial performance, was used to verify the nomological validity of this new construct. Findings – The results of this study suggest that the effectiveness of management accounting systems can be measured using a second-order construct. This construct includes 14-items, covering four dimensions of the management information characteristics. Research limitations/implications – Although contributing to the advancement of knowledge, it is, however, limited to the Portuguese organizational environment and culture. Therefore, further studies should be carried out in other organizational contexts and cultures, to test and validate this multidimensional tool. Practical implications – The multidimensional tool presented and validated in this study can be used by executives of SMEs for assessing the effectiveness of their management accounting systems, which can help to improve SMEs' performance measurement and benchmarking processes. Originality/value – On the best of our knowledge, this is the first study wherein the MAS is modeled as a second-order construct from the perspective of multidimensional information characteristics. This second-order approach recognizes the contribution and retains the distinctive nature of each first-order construct, representing the management accounting system. This multidimensional construct could be very important for future research by allowing to capture synergies resulting from the balanced development of its four information dimensions, and consequently, offer new contributions to management accounting knowledge.